Marketing of hair sheep production in municipalities of Tejupilco y Amatepec of the State of Mexico. - Hernández-Martínez, Juvencio (2013)
The objective of this work was to determine the marketing of hair sheep in the south of the State of Mexico. The marketing process of sheep hair was analyzed in the municipalities of Tejupilco and Amatepec during 2011, through which the marketing channels and marketing margins were calculated in absolute and relative terms by their equivalent values to sheep meat. The information was obtained through sampling by intent, whereby 22 sheep producers, 7 collectors and 4 barbacoeros (barbeque seller) were surveyed. Information on prices, costs and sales volumes of each participating agent among other variables was collected. The results show that marketing of sheep was carried out through intermediaries (79%), while 21% of the sale of the herd was made directly to the final consumer. Regarding the marketing margins, the producer obtained 17.75% of the final price paid by the consumer. Intermediaries (barbeque and live sheep gatherer) obtained the highest marketing margin (82.24%). The barbacoero obtained the highest benefit: cost ratio. The most common marketing channel was the producer, sheep gatherer, barbacoero and final consumer.